2018
DOI: 10.15295/bmij.v6i1.229
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Media Marketing Activities on Brand Awareness, Brand Image and Brand Loyalty

Abstract: The aim of this research is to examine the effect of social media marketing activities on brand awareness, brand image and brand loyalty. In addition, it has been aimed to analyze the effect of brand awareness and brand image on brand loyalty in this research. The population of the research consists of the consumers who actively follow five brands with the highest social score according to the Marketing Turkey social media brand performance data on social media communication channels such as Facebook, Twitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
180
4
49

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(421 citation statements)
references
References 45 publications
24
180
4
49
Order By: Relevance
“…Many consumers turn to various types of social media to get information, because consumers consider the source of information more reliable than company-sponsored communication through traditional promotions. Advertisement as a component refers to ad campaigns and promotions that have been carried out by business people through social media to increase sales (Bilgin, 2018). Duffett (2017) and Alalwan et al (2017) performed a survey on the effect of advertising or social media advertising on perception and customer awareness and reported that advertising is an important part of social media marketing activities.…”
Section: Social Media Marketing Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Many consumers turn to various types of social media to get information, because consumers consider the source of information more reliable than company-sponsored communication through traditional promotions. Advertisement as a component refers to ad campaigns and promotions that have been carried out by business people through social media to increase sales (Bilgin, 2018). Duffett (2017) and Alalwan et al (2017) performed a survey on the effect of advertising or social media advertising on perception and customer awareness and reported that advertising is an important part of social media marketing activities.…”
Section: Social Media Marketing Activitymentioning
confidence: 99%
“…6 items of questions about Entertainment, Interaction and Trendiness were taken from a research conducted by Kim and Ko (2012). And 4 questions about Customization and Advertisement were adapted from studies conducted by Bilgin (2018). And then, there are 7 questions about Brand Equity obtained from Aaker (1996) and 2 questions from Seo and Park (2018).…”
Section: -Point Likert Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Selanjutnya, penelitian Kristiani dan Dharmayanti (2017) menunjukkan bahwa social media marketing memiliki pengaruh terhadap brand image. Beberapa penelitian lain juga menyimpulkan bahwa social media marketing memiliki pengaruh terhadap brand image (Bilgin, 2018;Wijaya & Putri, 2013;Perera & Perera, 2016).…”
Section: Pengaruh Social Media Marketing Terhadap Brand Imageunclassified
“…From the company's perspective, social media has become an important part of brand communications and marketing activities for businesses today, offering the opportunity to perform actions such as creating brand profiles, online customer service, product information and offering special offers to customers at low cost (Gallaugher and Ransbotham, 2010;Tsimonis and Dimitraidis, 2014;Breitsohl et al, 2015;Seo and Park, 2018). The studies show that social media marketing activities are highly functional for businesses in brand communication, brand value, brand identity and brand loyalty (Baird and Parasnis, 2011;Kim and Ko, 2012;McCann and Barlow, 2015;Dutot and Bergeron, 2016;Bilgin, 2018). From a consumer perspective, social media is a communication channel that facilitates communication with other consumers and reflects consumer habits, preferences, thoughts, feelings, and experiences from the consumers' point of view (Gallaugher and Ransbotham, 2010;Hajli, 2013).…”
Section: Introductionmentioning
confidence: 99%